IMPLEMENTASI MITIGASI RISIKO DENGAN METODE HOUSE OF RISK (HOR) PADA MATERIAL ALUMINIUM FOIL PRODUK RETAIL DI PT X. - Santoso, Peter Omega; Febryanto, Indra Dwi (University of Riau Kepulauan, 2025)
The increasing demand for retail products at PT X has led to a growing need for various types of packaging materials, particularly aluminum foil. This rising demand introduces several potential risks in the procurement process that may disrupt operational continuity and supply chain efficiency. This study aims to analyze the risks involved in procuring aluminum foil packaging and to identify key risk agents that should be prioritized in mitigation efforts. The method used is the House of Risk (HOR), a structured approach that maps the relationship between risk events and risk agents to develop appropriate mitigation strategies. Data were collected through interviews, direct observation, and questionnaires involving relevant stakeholders in the procurement process. The analysis identified 32 risk events associated with 32 risk agents. Based on the risk priority index, 12 mitigation strategies were proposed for implementation. These strategies are expected to help PT X minimize procurement disruptions, improve risk control, and ensure the continuity and sustainability of the company’s aluminum foil packaging supply chain.